Text searching algorithm using boyer moore horspool (BMH) algorithm - Siti Nurafiqah, Jaafar (2015)
The text searching is one of the famous technique uses to find data or text from the system for faster searching. Search algorithm is also known as a universal problem solving mechanism. We study about the selected technique which is Boyer Moore Horspool algorithm that used for searching the occurrences of a pattern (keyword) in a random text in medical database. The matching between these two words which is pattern and text are analyze by display the accuracy percentage. The objective of this study is to develop a searching function using Boyer-Moore Horspool algorithm based on keyword in a medical database. Therefore, we intend to provide an automatic search routine in the medical first aid application and evaluate performance of the proposed searching algorithm through character match percentage. Based on the study, the average analysis result for this algorithm is 93% which is a strong match.